Aesthetic Nasal Lobule Correction Using a Three-Dimensional Printed Polycaprolactone Implant. Issue 8 (November 2021) - Wee, Syeo Young; Kim, Tae Hyung; Kang, Hee Yong; Park, Eun Soo
Abstract : Abstract: Nasal tip plasty is a surgery that determines important rhinoplasty outcomes. A variety of autologous and alloplastic implants are utilized in this procedure, including 1 synthetic material known as polycaprolactone (PCL). This study provides background on the ready-made three-dimensional printed PCL implant for nasal lobule correction, before discussing the usefulness and effectiveness of the implant. A total of 23 patients who visited our hospital between January 2018 and January 2020 were evaluated in this study. We used 3 types of PCL implant to get an ideal shape for the nasal tip: tipball (globular shape), droneball (rugby ball shape), and dumbbell (dumbbell shape). The authors compared nasolabial angle and tip projection at the preoperative and postoperative period via photographic anthropometric analysis. In 4 patients, we also examined the dead space between the implant and soft tissue via ultrasonography. The follow-up period averaged 9.5 months and no serious complications were found after surgery. The nasolabial angle and tip projection had an average postoperative increase of 6.4° and 0.044, respectively. Ultrasonography revealed the attachment of the implant at the insertion site and no dead space was found. This is the first attempt to apply a ready-made three-dimensional printed PCL implant to a nasal lobule correction procedure. As the implant was easy to use and showed good results, it may be useful for aesthetic purposes in future nasal tip plasty procedures. Abstract : Supplemental Digital Content is available in the text